Do Poverty Traps Exist? - Kraay, Aart (World Bank, Washington, DC, 2014)
This paper reviews the empirical evidence on the existence of poverty traps, understood as self-reinforcing mechanisms through which poor individuals or countries remain poor. Poverty traps have captured the interest of many development policy makers, because poverty traps provide a theoretically coherent explanation for persistent poverty. They also suggest that temporary policy interventions may have long-term effects on poverty. However, a review of the reduced-form empirical evidence suggests that truly stagnant incomes of the sort predicted by standard models of poverty traps are in fact quite rare. Moreover, the empirical evidence regarding several canonical mechanisms underlying models of poverty traps is mixed.